(untitled) (Lex localis - Journal of Local Self-Government, 2019)
The role of Local Self-Government is essential for the promotion and protection of Human Rights. In the EU, regardless of all States being bind to the same sources of law in such matter, the intervention of the local authorities dependents on the functions to those attributed by the National Constitution. The engagement with of Human Rights of the local authorities may be looked as an obligation, based on legal reasoning that links the local authorities to the broader State to act. Although the primary responsibility for the promotion and protection of human rights rests with the State, the promotion of a human rights culture within local public services plays a vital role in promoting respect for and the realization of human rights in the society.